ANALISIS FAKTOR-FAKTOR PENENTU LOYALITAS PELANGGAN PADA KORAN PT TIMIKA GRAFIKA EXPRESS - Ira Safitri; Muh Sabir (CV. Adiba Aisha Amira, 2024)
This research aims to determine the determining factors of customer loyalty in the PT Timika Graphics Express newspaper. The research method used in this research is descriptive. The data collection techniques in this research are observation techniques and distributing questionnaires to Timika Express newspaper subscribers. The analytical tool in this research uses factor analysis. Based on the results of the analysis, it shows that product quality factors, promotion factors and price factors are the determining factors for PT customer loyalty. Timika Express.